Uma Viagem Com Calvino: Passeios Entre Literatura, Crítica e Ensaística - Guarda, Alessandra Camila Santi (2020)
This research aims to deepen studies on the work of Italo Calvino, for this purpose, it is intended to verify and analyze which themes and aesthetic elements are recurrent in Italo Calvino’s essay and literary production, which characterize him as contemporary, in the terms proposed by Giorgio Agamben. The study is based on the essay production of Calvino and the work Il visconte dimezzato (1952), part of the I nostri antenati (1960) trilogy, more specifically, we verify how the ideas developed by Calvino on literature are articulated with his own literary work. We look for theoretical basis in the conceptual elaborations on the notion of contemporary in Giorgio Agamben, since we understand that such elaborations help us to reflect on the critical and literary production in the context of the humanities, with which Calvino contributed in works such as Seis propostas para o próximo milênio (1990) and Por que ler os clássicos (1993). From his literary and essayistic production, texts that present conceptual formulations that are dear to the studies of literature and literary criticism stand out in the contemporary world. Mainly, we observe that thinking about what constitutes the contemporary was a constant for Calvino, like the Seis propostas para o próximo milênio and the essays compiled in the books Assunto encerrado (2009), Coleção de areia (2010), Mundo escrito e mundo não escrito (2015). Also, the correspondence of Italo Calvino, Lettere 1940-1985 (2000), contemplates the desire to devise aesthetic and philosophical categories to understand the literary production and other artistic languages of his time. Considering the style of the narrative Il visconte dimezzato, we chose the values Lightness and Multiplicity linked to combinatorial art, as categories of analysis of this work. The research is theoretically and analytically guided by the multiple field of literature and other areas of knowledge, and in the relation between contemporary literature and philosophy.